Media Convergence as Universities’ Attraction: Study of the Use of E-Learning as a Marketing Communications Strategy of Private Higher Education Institution in Indonesia - Siti Komsiah; Eli Jamilah Mihardja; Dian Harmaningsih (Communication Sphere, 2015)
ABSTRACTThe competition between higher education institutions in attracting prospective studentsincreased today. Each educational institution improve educational facilities and infrastructurefacilities, improvement of the curriculum, the quality of human resources, collaborate withoutside agencies, and emphasis the cost of education. The increase in the facility includes theapplication of e learning on the course. E learning application provides convenience andflexibility in teaching and learning activities. This paper is a presentation on marketingcommunications strategies using e learning in the lecture as an attraction for students,consumers of higher education institutions.This research using survey method of students and then depth interviews withmanagers of private universities whose implementing e learning programs in Indonesia. At thetime of this paper was written, research was already held in Jakarta (representing the westernregion), Denpasar (representing the middle region), and will soon be carried out in Makassar(representing the eastern region of Indonesia).Our preliminary study, in Jakarta and Denpasar resulted in findings that e learning canbe partially marketing communications strategies for Private Higher Education Institution. Thatis, the application of e learning as a teaching and learning method improve the Private HigherEducation Institution opportunity to be selected as a college by students. The findings of thisstudy academically useful as a reference for similar studies in the future. As a practical manner,the findings of this study are expected to be a recommendation for the management of otherprivate universities in shaping the marketing strategy of the institution.Keywords: E learning, Marketing Communication Strategy, Private Higher Education Institution